Digital Leadership and Strategic Transformation in Incumbent Organizations: A Systematic Literature Review - Dewayanto, Totok; Luhgiatno (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
Incumbent organizations face a paradox that digital-native ﬁrms do not: they must transform the very structures that made them viable in the ﬁrst place. This systematic literature review synthesizes 44 peer-reviewed sources across two analytical layers a PRISMA 2020 protocol covering Scopus (1990–2020), and a complementary thematic synthesis of literature published between 2014 and 2024 to map the mechanisms through which digital leadership drives strategic transformation in established ﬁrms. Three propositions, grounded in a Middle Range Theory (MRT) framework, organize the analysis: (1) co-creation strategy mediates the path from digital leadership to business model innovation, contingent on modular system architecture; (2) intellectual debate intensity between middle and top management determines whether organizations successfully traverse the "Valley of Death" at strategic inﬂection points; and (3) modular, reconﬁgurable architecture moderates digital leadership's eﬀect on organizational agility. Beyond these mechanisms, the review identiﬁes the "Digital Paradox"  the observed failure of heavy technology investment to produce strategic change when leadership architecture remains unchanged and ﬁnds that ambidextrous leadership resolves it by simultaneously exploiting current capabilities while building new digital competencies. The MRT framework conﬁrms that traditional leadership theory retains explanatory power in algorithmically mediated structures, provided its boundary conditions are adjusted for distributed authority and recursive technology-social inﬂuence dynamics. Practical recommendations focus on two organizational prerequisites: psychologically safe environments where middle managers can challenge strategic assumptions, and deliberate investment in service-oriented, modular technology infrastructure.